GROWTH MINDSET TRAINING TO DEVELOP TUTORS’ MIND PATTERNS IN NON-FORMAL EDUCATIONAL INSTITUTIONS: PELATIHAN GROWTH MINDSET UNTUK MENGEMBANGKAN POLA PIKIR TUTOR DI LEMBAGA PENDIDIKAN NONFORMAL - M Wagio; Choirun Nisaa’ (Jurnal Obor Penmas: Pendidikan Luar Sekolah, 2026)
The problems faced by tutors at CLC (Community Learning Centers) are diverse and have the potential to influence their mindset in carrying out their teaching duties. This study aims to describe the process of service through growth mindset training and analyze its contribution to the development of tutors’ mindsets. The research approach used is qualitative with triangulation of data collection techniques, namely interviews, observation, and documentation. The results show that growth mindset training can change the tendency of tutors’ mindsets, which were previously closer to a fixed mindset, to a growth mindset. This change emerged through a series of training activities, including the formulation of problems experienced by tutors, material preparation, sending permission letters, the dissemination process, and verbal evaluation with training participants. These findings confirm that growth mindset training contributes positively to strengthening tutors’ ability to see challenges as opportunities for growth, thereby supporting the improvement of learning quality at CLC.